OS DESAFIOS DO ATENDIMENTO EDUCACIONAL ESPECIALIZADO (AEE) NO CONTEXTO PANDÊMICO - Lucion, Daiane Carvalho (2023)
The main objective of this study was to analyze the challenges faced by special education teachers from public schools in São Sepé/RS, in the Specialized Educational Service (SES) in the pandemic context. Specifically, the objectives were to identify the repercussions of the Covid-19 pandemic on the SES in the context of teaching through the state of knowledge; to reflect on the pedagogical practices developed by special education teachers during the Covid-19 pandemic; and to know the legal regulations produced in the pandemic period to guide the operation of SES via remote teaching. The research is characterized as a case study with a qualitative methodological approach. Data collection was carried out in the second semester of 2022. To contemplate the objectives outlined for this research in the first moment a theoretical review was conducted, the search for bibliographic materials was in databases such as SciELO and Google Scholar. In the second moment of the research, an on-line questionnaire was applied to a sample of special education teachers from public schools in São Sepé/RS. Afterwards, a documental analysis of the legal norms produced in the pandemic period to guide the operation of SES via remote teaching was carried out. It is worth pointing out that many challenges were faced during the pandemic period, the remote teaching established by higher education agencies allowed students with or without disabilities not to be unprotected in their learning process, but many obstacles interfered with this path to achieve a satisfactory learning, such as socioeconomic conditions, lack of human resources, lack of professional training, lack of access to digital technologies, family instruction, pedagogical adaptations, and quality public policies. As for the reflection on the pedagogical practices developed by the teachers in the context of remote teaching, there was an investment in training courses to face the challenges that presented themselves, to minimize the impacts and effects of the pandemic context, seeking other strategies to enhance the students' learning, resulting in changes in teaching practices. As for the analysis of the norms produced for special education in the pandemic period to guide the operation of the SES, it was possible to identify that the policies guarantee that all students have access to school, learning, and full development, but it is noteworthy that the pedagogical practices for the target audience of Special Education still need to have a careful look, taking into account the construction of a more inclusive society, generating effective reflections of public agencies.